Pengaruh Kualitas Pelayanan dan Pengemasan Daya Tarik Wisata Terhadap Keputusan Berkunjung Serta Dampaknya pada Kepuasan Wisatawan di Museum Negeri Sonobudoyo Yogyakarta - Saputra, Eryd; Ambiyar, Ambiyar (Jurnal Master Pariwisata (JUMPA); Volume 06, Nomor 01, Juli 2019DO - 10.24843/JUMPA.2019.v06.i01.p10, 2019)
This research is conducted to determine effect of service quality and packaging of tourist attraction on visiting decisions and the impact on tourist satisfaction. This study uses a descriptive method with a quantitative approach where the results of this study are expected to provide useful strategic information in the management of the Sonobudoyo State Museum. The sample used in this study was 100 respondents taken based on the tourist population. In the discussion of this study, researchers used multiple regression analysis to determine the effect of independent variables on the dependent variable. The results of the study show simultan that there is a positive and significant influence between the variable quality of service and packaging of tourist attraction to visiting decisions and their impact on tourist satisfaction. The results of the analysis partially have the effect of variable service quality on tourist satisfaction that is not positive and significant. Keywords: Quality of Service, Packaging of Travel Attractions, Decisions Visit, Satisfaction of Travelers.